Integrated proteomic analysis to explore the molecular regulation mechanism of IL‐33 mRNA increased by black carbon in the human endothelial cell line EA.hy926. Issue 10 (1st July 2022) - Jiang, Wanyu; Chu, Hongqian; Li, Zekang; Ge, Jianhong; Wang, Xiaoyun; Jiang, Jianjun; Xiao, Qianqian; Meng, Qinghe; Lou, Yaxin; Hao, Weidong; Wei, Xuetao
Abstract: Black carbon (BC) correlates with the occurrence and progression of atherosclerosis and other cardiovascular diseases. Increasing evidence has demonstrated that BC could impair vascular endothelial cells, but the underlying mechanisms remain obscure. It is known that IL‐33 exerts a significant biological role in cardiovascular disease, but little is known about the molecular regulation of IL‐33 expression at present. We first found that BC significantly increased IL‐33 mRNA in EA.hy926 cells in a concentration and time‐dependent manner, and we conducted this study to explore its underlying mechanism. We identified that BC induced mitochondrial damage and suppressed autophagy function in EA.hy926 cells, as evidenced by elevation of the aspartate aminotransferase ( GOT2 ), reactive oxygen species (ROS) and p62, and the reduction of mitochondrial membrane potential (ΔΨm ). However, ROS cannot induce IL‐33 mRNA‐production in BC‐exposed EA.hy926 cells. Further, experiments revealed that BC could promote IL‐33 mRNA production through the PI3K/Akt/AP‐1 and p38/AP‐1 signaling pathways. It is concluded that BC could induce oxidative stress and suppress autophagy function in endothelial cells. This study also provided evidence that the pro‐cardiovascular‐diseases properties of BC may be due to its ability to stimulate the PI3K/AKT/AP‐1 and p38/AP‐1 pathway, further activate IL‐33 and ultimately result in a local vascular inflammation.